Правовий і політичний компроміс. - Некіга, С.М.; Некига, С.М.; Nekiga, S (My University, 2011)
Currently, the political and juridical sciences topical formulation of the problem is not so much on the elimination of political and legal conﬂ icts, much of their settlement, and special attention in the research process on a compromise. The article analyzes the political and legal compromise.
Некіга, С.М. Правовий і політичний компроміс.// Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 43. С. 164 - 173.
Keywords: Політичний компроміс; Компроміси; Політико - правові компроміси; Политико - правовые компромисы; Компромисы; Политический компромис; The political compromise; compromise; Politico - legal compromises